Balancing State Regulation and Sports Autonomy: Legal Implications of Indonesia’s Ministerial Regulation No. 14 of 2024 - Kasianus Joseph Junior Fenanlampir; Irmantara Subagio; Arinto Nugroho; Fatkur Rohman Kafrawi; Noortje Anita Kumaat; Achma Widodo (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. This study aims to examine the legal position and governance implications of the Minister of Youth and Sports Regulation Number 14 of 2024 within the Indonesian sports regulatory framework, with particular emphasis on the balance between regulatory standardization and organizational autonomy in achievement sports. The research seeks to assess the consistency of the regulation with higher-ranking national legislation and international sports governance principles, especially those embodied in lex sportiva and the Olympic Charter. Materials and methods. The study employs a qualitative normative–empirical approach. Normative analysis is conducted on primary legal materials, including Law Number 11 of 2022 on Sports, Government Regulation Number 46 of 2024, and the Ministerial Regulation Number 14 of 2024, supported by secondary legal sources and international sports governance instruments. Empirical data are collected through interviews and focus group discussions involving purposively selected stakeholders, including provincial sports organization administrators, sports law scholars, and sports governance practitioners. Data are analyzed using normative legal interpretation and thematic analysis, with triangulation applied to enhance analytical credibility. Results. The findings indicate that the ministerial regulation introduces administrative mechanisms that extend into internal organizational domains, such as leadership selection and organizational congresses, which are normatively protected under national sports law. Normative analysis reveals inconsistencies within the regulatory hierarchy, particularly regarding delegated authority and organizational autonomy. Empirical findings demonstrate that stakeholders perceive these regulatory mechanisms as reducing flexibility, generating interpretative ambiguity, and affecting governance stability. The integration of normative and empirical results shows a convergence between legal inconsistencies and practical uncertainty in sports governance. Conclusions. The study concludes that the governance of achievement sports in Indonesia is characterized by structural tension between regulatory standardization and organizational autonomy. While organizational autonomy is formally recognized within the national legal framework, it is subject to practical limitations arising from subordinate regulatory intervention. Regulatory incoherence not only undermines legal certainty but also affects institutional confidence and long-term governance sustainability. The findings underscore the need for regulatory approaches that respect hierarchical legal norms and international sports governance principles while preserving the operational autonomy essential for effective and sustainable sports governance.